Extraction and Evaluation of Fish Body Oil from Lesser Sardines Employing Different Extraction Methods - Raffi, S M (International Journal of Pharmaceutical & Biological Archive, 2016)
Extraction and Evaluation of Fish Body Oil from Lesser Sardines Employing Different Extraction Methods